Estudo de cortinas black-out como componentes no isolamento sonoro de fachadas - Pisani, Angela Paulina Grandeaux (2008)
Buildings which have high levels of sound pollution and facades that do not isolate outside noise are often found in large cities. This situation affects people s sound comfort and health. In connection with that, there is the high cost of materials which offer good sound reduction indices. This way, it is necessary to investigate alternative materials at lower costs, such as the blackout curtains. Taking these factors into consideration, the aim of this study is to examine the increase of sound isolation index (Rw) in relation to outside noise, through the use of vynil and polyester curtains in windows. The tests were carried out at the Acoustic Laboratory of the Federal University of Santa Maria. The results of the tests have shown the performance of various curtains arrangements, resulting in a 2 to 5 dB increase in the sound isolation index. Duplicating curtains enabled an increase of about 1 dB in relation to simple curtains. There was no increase in the sound isolation index when overlapping the curtains. Putting up glass wool panels of different thickness has not influenced in the facade sound isolation. With this study, it has been possible to quantify the improvement of facades sound isolation by putting up blackout curtains currently in the market.